Targeted biopsy in the detection of prostate cancer using an office based magnetic resonance ultrasound fusion device - Sonn, Geoffrey A; Natarajan, Shyam; Margolis, Daniel J A; MacAiran, Malu; Lieu, Patricia; Huang, Jiaoti; Dorey, Frederick J; Marks, Leonard S (The Journal of urology, 2013)
Targeted biopsy of lesions identified on magnetic resonance imaging may enhance the detection of clinically relevant prostate cancers. We evaluated prostate cancer detection rates in 171 consecutive men using magnetic resonance ultrasound fusion prostate biopsy. Subjects underwent targeted biopsy for active surveillance (106) or persistently increased prostate specific antigen but negative prior conventional biopsy (65). Before biopsy, each man underwent multiparametric magnetic resonance imaging at 3.0 Tesla. Lesions on magnetic resonance imaging were outlined in 3 dimensions and assigned increasing cancer suspicion levels (image grade 1 to 5) by a uroradiologist. A biopsy tracking system was used to fuse the stored magnetic resonance imaging with real-time ultrasound, generating a 3-dimensional prostate model on the fly. Working from the 3-dimensional model, transrectal biopsy of target lesions and 12 systematic biopsies were performed with the patient under local anesthesia in the clinic. A total of 171 subjects (median age 65 years) underwent targeted biopsy. At biopsy, median prostate specific antigen was 4.9 ng/ml and prostate volume was 48 cc. A targeted biopsy was 3 times more likely to identify cancer than a systematic biopsy (21% vs 7%). Prostate cancer was found in 53% of men, 38% of whom had Gleason grade 7 or greater cancer. Of the men with Gleason 7 or greater cancer 38% had disease detected only on targeted biopsies. Targeted biopsy findings correlated with level of suspicion on magnetic resonance imaging. Of 16 men 15 (94%) with an image grade 5 target (highest suspicion) had prostate cancer, including 7 with Gleason 7 or greater cancer. Prostate lesions identified on magnetic resonance imaging can be accurately targeted using magnetic resonance ultrasound fusion biopsy by a urologist in clinic. Biopsy findings correlate with level of suspicion on magnetic resonance imaging.